Osteoarthritis of the hip: the patient behind the disease. Issue 2 (April 1982) - Solomon, L; Schnitzler, C M; Browett, J P
Abstract : Previous epidemiological studies suggested that patients with osteoarthritis (OA) of the hip might constitute a definable subset of the population with characteristics that predispose them to joint failure. To investigate this possibility a comparative study of somatotype, bone density, disc degeneration, polyarticular joint degeneration, and soft-tissue calcification was carried out in 3 groups of individuals: (1) patients presenting with OA of the hip; (2) patients with acute femoral neck fracture; (3) healthy controls. OA of the hip was rare in patients with femoral neck fracture; conversely, patients with coxarthrosis did not have the low values for bone density seen in the fracture group. There were significant differences in somatotype in the 2 patient groups; 94% of those with OA were endomorphic mesomorphs. Polyarticular OA occurred with the same prevalence in the 2 groups of women, but among males there was a significantly greater involvement of knees and hands in the OA group than in the fracture group. The highest incidence of joint calcification was found in the fracture group and the lowest in the OA group. It was concluded that patients with OA of the hip form a definable subset of the general population. Within this group the appearances of hip OA are determined by 3 interacting factors: mechanical stress, cartilage degeneration, and bone response.